2022
DOI: 10.1507/endocrj.ej22-0237
|View full text |Cite
|
Sign up to set email alerts
|

Gestational trimester-specific reference ranges for serum thyrotropin and free thyroxine in Japanese

Abstract: Thyroid diseases in pregnant and lactating women may result in adverse outcomes for both mothers and infants. A reference range for thyroid function is required in different areas; however, few studies on the gestational change or reference ranges of thyrotropin (TSH) and free thyroxine (FT4) concentrations for Japanese pregnant women have been reported. To establish the gestational trimester-specific reference ranges of serum TSH and FT4 concentrations, our previously published data on 481 pregnant women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The established trimester-specific reference intervals differ from the fixed and established ones, which would significantly change the strategy for initiating pharmacotherapy in pregnant women. Comparable deviations from established TSH reference limits in pregnancy have been documented in studies from various countries, including Japan, Turkey, UAE, India, Korea, Brazil, Poland, Pakistan, and Chile [2,11,19,22,23,[31][32][33][34]. For instance, a study by Morais et al identified an upper limit for TSH in postnatal pregnant women corresponding to fixed reference ranges recommended by the ATA [24].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The established trimester-specific reference intervals differ from the fixed and established ones, which would significantly change the strategy for initiating pharmacotherapy in pregnant women. Comparable deviations from established TSH reference limits in pregnancy have been documented in studies from various countries, including Japan, Turkey, UAE, India, Korea, Brazil, Poland, Pakistan, and Chile [2,11,19,22,23,[31][32][33][34]. For instance, a study by Morais et al identified an upper limit for TSH in postnatal pregnant women corresponding to fixed reference ranges recommended by the ATA [24].…”
Section: Discussionmentioning
confidence: 97%
“…According to guidelines published by ETA, ATA, and the Endocrine Society, the upper reference interval for TSH during the first trimester remained at 2.5 mIU/L for an extended period [3][4][5]. However, many studies published after 2011 indicate that this limit increases the diagnosis of subclinical hypothyroidism, leading to overdiagnosis and unnecessary treatment [11,12,[15][16][17][18][19]. Furthermore, TSH levels associated with FT4 reduction typically fall between 4 and 5 mIU/L.…”
Section: Introductionmentioning
confidence: 99%